The Level of Lactic Acidosis Affects Lactate Minimum in a Heart Rate-Based Lactate Minimum Test - Labruyère, R.; Perret, C. (International Journal of Sports Medicine, 2012)
The aim was to investigate whether the level of lactic acidosis in the first part of a heart rate-based lactate minimum test affects the lactate minimum heart rate and performance. We tested 15 men (age: 31±6 years, height: 179±6 cm, body mass: 75.6±7.6 kg and V˙O2peak 50.3±10.0 ml · min − 1 · kg − 1). They all completed 2 lactate minimum tests following 2 different protocols during the first part of the test, i. e., i) a maximal test until exhaustion to provoke extensive lactacidaemia and ii) a submaximal test abandoned 3 stages earlier than the maximal test to provoke significantly lower but still considerable lactacidaemia. The second part of the lactate minimum test was identical for both runs. It consisted of a heart rate-based incremental test to determine the lactate minimum and the corresponding lactate minimum heart rate and performance. Results showed a significantly higher maximal blood lactate concentration at the end of the maximal test compared to the submaximal test (9.7±2.7 vs. 6.0±2.0 mmol · l − 1, P<0.001). Also mean lactate minimum heart rate (160±12 vs. 144±13 bpm, P<0.001) and performance (200±40 vs. 170±35 W, P<0.001) were significantly higher after the maximal test compared to the submaximal test. We conclude that the first part of the heart rate-based lactate minimum test needs to be performed until exhaustion to receive reliable and meaningful results.
Keywords: exercise test; validity; test protocol; endurance; cycling